The Influence of Motivation and Work Ethics on Employee Performance Through Work Behavior as an Intervening Variable at PT. Prima Land, Pandeglang Regency - Kamilasari, Tria; Prahiawan, Wawan; Maria, Vera (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to determine the influence of Motivation and Work Ethics on Employee Performance Through Work Behavior as Variable Intervening at PT. PrimaLand Pandeglang Regency. The method used in this research is quantitative with a descriptive approach. The population in this study were 81 employees at PT. PRIMALAND. This research sample uses the entire research population using satureted sampling. Data analysis techiques in this research use